The CD38/NAD/SIRTUIN1/EZH2 Axis Mitigates Cytotoxic CD8 T Cell Function and Identifies Patients with SLE Prone to Infections - Eri Katsuyama (Cell Reports, 2020)
Summary: Patients with systemic lupus erythematosus (SLE) suffer frequent infections that account for significant morbidity and mortality. T cell cytotoxic responses are decreased in patients with SLE, yet the responsible molecular events are largely unknown. We find an expanded CD8CD38high T cell subset in a subgroup of patients with increased rates of infections. CD8CD38high T cells from healthy subjects and patients with SLE display decreased cytotoxic capacity, degranulation, and expression of granzymes A and B and perforin. The key cytotoxicity-related transcription factors T-bet, RUNX3, and EOMES are decreased in CD8CD38high T cells. CD38 leads to increased acetylated EZH2 through inhibition of the deacetylase Sirtuin1. Acetylated EZH2 represses RUNX3 expression, whereas inhibition of EZH2 restores CD8 T cell cytotoxic responses. We propose that high levels of CD38 lead to decreased CD8 T cell-mediated cytotoxicity and increased propensity to infections in patients with SLE, a process that can be reversed pharmacologically. : Katsuyama et al. find that an expanded CD8CD38high T cell population in SLE patients is linked to infections. CD8CD38high T cells display decreased cytotoxic capacity by suppressing the expression of related molecules through an NAD+/Sirtuin1/EZH2 pathway. EZH2 inhibitors increase cytotoxicity offering a means to mitigate infection rates in SLE. Keywords: systemic lupus erythematosus, patients, CD8 T cell, CD38, cytotoxicity, infection, nicotinamide adenine dinucleotide, Sirtuin1, EZH2